Respuesta :
Step-by-step explanation:
Simplifying
f(x) = 5x + -3(3x + 7)
Multiply f * x
fx = 5x + -3(3x + 7)
Reorder the terms:
fx = 5x + -3(7 + 3x)
fx = 5x + (7 * -3 + 3x * -3)
fx = 5x + (-21 + -9x)
Reorder the terms:
fx = -21 + 5x + -9x
Combine like terms: 5x + -9x = -4x
fx = -21 + -4x
Solving
fx = -21 + -4x
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Divide each side by 'x'.
f = -21x-1 + -4
Simplifying
f = -21x-1 + -4
Reorder the terms:
f = -4 + -21x-1